2005
DOI: 10.22358/jafs/67153/2005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary conjugated linoleic acid on laying hen performance, egg yolk fatty acid composition and egg quality during refrigerated storage

Abstract: Sixty-four Lohman LSL white layers, 75 weeks of age, kept in individual cages were assigned randomly to four treatments of 16 hens per group. The hens received one of four diets with 0, 0.5, 1 or 2% CLA for 4 weeks. Eggs were collected daily and stored at 4 o C for 1 or 42 days. The performance of hens and fatty acid composition, thiobarbituric acid reactive substances (TBARS) levels, pH of yolk and albumen, and yolk colour in eggs were measured.Feed intake, feed conversion and egg weight were influenced by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Both dietary and oral supplementation of vitamin E has been shown to immensely improve livestock performance and their products (Figure ). Vitamin E supplementation in animal diet has been reported to be effective in reducing lipid oxidation in meat (Gallardo et al, ; Macit et al, ), egg (Bölükbaşi, Erhan, Keleş, & Koçyiği, ), and milk (Santos et al, ), as well as lowering serum and egg yolk cholesterol concentrations and improving antioxidant status of the animal (Sahin et al, ; Santos et al, ). Other reports also revealed that dietary vitamin E can increase the level of sex hormones (Franchini et al, ), hatchability, and fertility (Ipek & Dikmen, ) of livestock.…”
Section: Introductionmentioning
confidence: 99%
“…Both dietary and oral supplementation of vitamin E has been shown to immensely improve livestock performance and their products (Figure ). Vitamin E supplementation in animal diet has been reported to be effective in reducing lipid oxidation in meat (Gallardo et al, ; Macit et al, ), egg (Bölükbaşi, Erhan, Keleş, & Koçyiği, ), and milk (Santos et al, ), as well as lowering serum and egg yolk cholesterol concentrations and improving antioxidant status of the animal (Sahin et al, ; Santos et al, ). Other reports also revealed that dietary vitamin E can increase the level of sex hormones (Franchini et al, ), hatchability, and fertility (Ipek & Dikmen, ) of livestock.…”
Section: Introductionmentioning
confidence: 99%
“…It was determined that the addition of 0.5 mL kg −1 PSO to the diet significantly decreased the rate of damaged eggs and the shell-breaking strength (P < 0.05). In addition to studies reporting that dietary CLA levels improve egg quality (Bölükbaşı and Erhan, 2005), there are also studies that report the negative effects on egg quality such as the Hough unit, shell-breaking strength, and egg hardness (Kim et al, 2007;Franczyk-Zarow et al, 2008). In this study, the damaged egg ratio and shell-breaking strength were adversely affected only in the 0.5 mL kg −1 PSO group.…”
Section: Resultsmentioning
confidence: 60%
“…One of these biologically active components used in research is conjugated linoleic acid (CLA), which has many health benefits. However, there have been studies reporting that CLA added to the diet of laying hens has some negative effects on egg quality (Ahn et al, 1999;Kim et al, 2007;Franczyk-Zarow et al, 2008) as well as beneficial effects (Bölükbaşı and Erhan, 2005). Recently, there has been interest in conjugated linolenic acid (CLnA), due to its very important phys-iological properties.…”
Section: Introductionmentioning
confidence: 99%